De la politique de la rue à la lutte institutionnelle : le témoignage de deux militantes à travers le livre politique - Ludivine Thouverez (Amnis)
The institutionalization of some post-2008 social movements has led to the emergence of a new elite. Their codes and discourse are intended to break with those of traditional parties. Catherine Dorion of Québec Solidaire and Gala Pin of Barcelona en Comú are two examples of women, feminists, and activists, who decided to take up political office and recount their experiences of institutional life in the autobiographical works Les Têtes Brûlées and ¿Qué pinto yo aquí? Drawing on the theoretical contributions of Christian Le Bart, this paper examines whether the writing of these two activists breaks with the canon of the usual political books and reflects an evolution in political practice over the last decade. We shall see these authors distinguish themselves by rejecting prevailing attitudes and viewing writing as a tool for self-assertion, temporal deceleration, and bodily reclamation.